Star Hotel Occupancy Fluctuations in Makassar: Evidence from BPS Data and Implications for Islamic Tourism Marketing - Fajar Rakasiwi Syamsuddin (Indonesian Journal of Islamic Economics and Finance, 2026)
Occupancy rates of star hotels in Makassar fluctuate substantially; however, empirical patterns remain poorly documented due to the absence of systematic analysis of official data. This research gap necessitates a structured empirical investigation. This study empirically examined monthly occupancy fluctuations from March 2024 to June 2025 using secondary data from BPS (Central Bureau of Statistics). A qualitative document analysis was employed, involving month-to-month change calculations, peak and trough identification, and recovery pattern assessments. The findings revealed occupancy ranging from a peak of 59.32 percent in August 2024 to a trough of 32.30 percent in March 2025, representing a range of 27.02 percentage points. The market demonstrated rapid recovery, regaining over 70 percent of lost occupancy within one month. Notably, three months were missing from the data series. From an Islamic business ethics perspective, the sharp Ramadan trough requires fair treatment of workers and the avoidance of exploitative price hikes during peak periods such as August. Marketing strategies must uphold amanah (trustworthiness) by transparently reporting data gaps and maslahah (public interest) by ensuring promotional campaigns benefit local communities, not just hotel profits. The novelty of this study lies in integrating empirical occupancy fluctuation analysis with Islamic business ethics principles specifically justice, trustworthiness, and public interest into tourism marketing strategy, an approach absent in previous research. The study concludes that strengthening evidence-based marketing requires understanding peak, trough, and recovery patterns while improving data completeness and embedding Islamic ethical principles into every strategic decision.